Six weeks that changed the preterm infant brain: lessons learned from the Family Nurture Intervention randomized controlled trials - Ludwig, Robert J.; Myers, Michael M.; Welch, Martha G. (Frontiers in Psychology, 2025)
Aim We review extensive results from two randomized controlled trials conducted over 9 years, comparing standard care (SC) in level-4 neonatal intensive care units (NICUs) with SC plus Family Nurture Intervention (FNI). Methods FNI included ~six weeks of facilitated mother-infant interactions aimed at achieving mother-infant ‘autonomic emotional connection’, a novel construct that describes the emotional mother-baby relationship at the level of the autonomic nervous system. Results and conclusion Thus far, 18 peer-reviewed publications documented significant positive short-and long-term effects of FNI on infant neurobehavioral functioning, developmental trajectories and both mother and child autonomic health through five years. The observed profound effects of FNI on central and autonomic nervous system function following a relatively short intervention support a novel autonomic theory of emotions. We discuss the theoretical and clinical advances that grew out of the trials and speculate on how FNI changes the mother-infant relationship from ‘dysregulation’ to autonomic emotional co-regulation. We review new constructs and tools that can be used to view and measure the mother-infant autonomic emotional relationship. We present a simple blueprint to improve preterm birth outcomes. Finally, we discuss the significance of our findings and possible impact on the future of preterm infant care worldwide.